2020
DOI: 10.21203/rs.3.rs-78208/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

YAP Manipulates Proliferation Via PTEN/AKT/mTOR-mediated Autophagy in Lung Adenocarcinomas

Abstract: Background: Autophagy is a double-edged sword during the initiation or progression of multiple tumors. Hippo pathway core-factor YAP has been proved to be involved in autophagy processes. The present study aimed to identify the mechanism underlying modulation of YAP via PTEN/AKT/mTOR-mediated autophagy in lung adenocarcinomas (LUAD).Methods: Data of LUAD chip GSE43458 was obtained from Gene Expression Omnibus (GEO). RT-qPCR and Western blot were used to assess YAP expression in LUAD cell lines. CCK-8 assay, fl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…In A549 lung cancer cells, upregulation of YAP is associated with increased phosphorylation of AKT and resistance of cancer cells. 126 It was suggested that modulation of YAP by curcumin is a mechanism for activation of cancer cell death and reduction of cancer resistance through autophagy. So far, few studies evaluating the role of curcumin in the modulation of autophagy through YAP pathway have been conducted.…”
Section: Role Of Yes-associated Protein In Curcumin-induced Autophagymentioning
confidence: 99%
“…In A549 lung cancer cells, upregulation of YAP is associated with increased phosphorylation of AKT and resistance of cancer cells. 126 It was suggested that modulation of YAP by curcumin is a mechanism for activation of cancer cell death and reduction of cancer resistance through autophagy. So far, few studies evaluating the role of curcumin in the modulation of autophagy through YAP pathway have been conducted.…”
Section: Role Of Yes-associated Protein In Curcumin-induced Autophagymentioning
confidence: 99%
“…Oppositely, autophagy can also provide nutrition to support cancer cell survival. Studies indicated that autophagy promotes LUAD cell proliferation and tumor xenograft growth [25]. In our study, CCL20 is negatively correlated with autophagy pathways, and the underlying molecular needs more exploration.…”
Section: Discussionmentioning
confidence: 67%
“…Nazim et al (2017) reported inhibition of Akt/mTOR promoted cell death in human lung adenocarcinoma cells through activating autophagy flux. Xu et al (2021) also demonstrated hippo pathway effector YAP could induce activation of Akt/mTOR signaling pathway to regulate cell proliferation via autophagy in lung adenocarcinomas. Increasing evidence has also showed the regulatory association between Akt/mTOR signaling pathway and autophagy in lung adenocarcinomas (Chen et al, 2017; Huo et al, 2016; Jian et al, 2019; Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 98%